EFFICIENCY OF USING WINTER INTERMEDIATE CROPS FOR GREEN FEED - Храмов, Ю.В.; Свистунова, Ирина; Троян, В.И. (SWorldJournal, 2020)
This article provides a detailed analysis of the profitability of growing winter intermediate crops for green fodder in the Right-Bank Forest-Steppe of Ukraine. It has been established that the use of winter wheat on green fodder is economically inefficie